Pengaruh Kualitas Layanan terhadap Kepuasan Pelaksanaan Program MBKM - Yulia, Iis Anisa; Mutmainah, Isbandriyati; Marnilin, Feni; Mahfudi, Ahmad Zaid (Jurnal Ilmiah Manajemen Kesatuan, 2022)
ABSTRACT Service quality and student satisfaction are important aspects of the strategy of higher education institutions in the competitive higher education market. One of the quality of higher education services that needs attention is the quality of service in the learning process. Merdeka Belajar Kampus Merdeka (MBKM) is a program launched by the Ministry of Education, Culture, Research and Technology as a service for students by providing opportunities for students to hone skills according to their interests and talents with various programs. The Faculty of Economics and Business UNB has organized the MBKM program since 2020/2021 with two programs, namely Student Exchange and KKNT. This study aims to determine the level of student satisfaction with the quality of service implementation of the MBKM program. This study uses census data, the analytical methods used multiple linear regression. Based on the results of t-test here are three variables that effect i.e. variable Tangibles, Reliability and Responsiveness while variable Assurance, Emphaty and Relevance does not affect the satisfaction of the implementation of the MBKM program. The result of this research was based on the F-test is the quality of service which consists of Tangibles, Reliability, Responsiveness, Emphaty, Assurance, and Relevance take effect simultaneously to satisfactions of the implementation of the MBKM program. Keywords : Service quality; Satisfaction; MBKM